Nomenclatural changes in the Australasian gall-inducing genus Apiomorpha Rübsaamen (Hemiptera: Coccomorpha: Eriococcidae) - Mills, Penelope J.; Gullan, Penny J.; Cook, Lyn G. (Zootaxa, 2017)
Apiomorpha Rübsaamen, 1894 was erected as a replacement name for Brachyscelis Schrader, 1863 that was preoccupied in the Coleoptera (Chrysomelidae: Brachyscelis Germar, 1834). Apiomorpha is a genus of eriococcid scale insects that induce galls on Eucalyptus (Myrtaceae) in Australia and New Guinea (Szent-Ivany & Womersley 1962; Gullan 1984; Gullan et al. 2005). In his original description of the genus, Schrader (1863a) included six species, of which B. citricola Schrader was subsequently recognised as a nomen nudum (Froggatt 1921). Among the other five, B. pileata Schrader was later designated as the type species of Apiomorpha by Lindinger (1937). Also amongst these five was B. ovicola Schrader, for which Schrader described and illustrated galls of males and females on twigs and leaves of Eucalyptus haemastoma (Schrader 1863a, plate II, figs a, e) in or near Sydney, New South Wales (NSW). He stated that his species names reflected the shape of the galls of adult females; hence those of B. ovicola can be interpreted as being egg-shaped and were illustrated as such by Schrader (1863a). Galls of males of B. ovicola he described and illustrated as trumpet-shaped.